Shoutai pills for treating recurrent miscarriage: a systematic review and meta-analysis of the safety and clinical efficacy in 11 randomized controlled trials - Ruan, Lijun; Cai, Ying; Yin, Yuan; Liu, Fang; Li, Minyi; Lu, Guangming (Frontiers in Pharmacology, 2025)
BackgroundDespite centuries of empirical use in Traditional Chinese Medicine (TCM) for miscarriage prevention, Shoutai Pills lack comprehensive scientific validation to support their widespread clinical application. Current evidence regarding their safety profile remains limited.MethodsFollowing PRISMA guidelines, we conducted a systematic review of randomized controlled trials (RCTs) from PubMed, Embase, Cochrane Library, CNKI, and Wanfang up to October 2024. Eligible studies evaluated Shoutai Pills as monotherapy or adjunctive treatment for recurrent miscarriage, reporting outcomes including safety (adverse events), live birth rate, pregnancy retention rate, TCM syndrome scores, and serum D-dimer levels. Meta-analyses were performed using random-effects or fixed-effect models, with heterogeneity assessed via I2 statistics.ResultsEleven RCTs (n = 888 participants) met inclusion criteria. No significant difference in overall adverse events between groups (RR = 0.91, 95% CI: 0.53–1.57; p = 0.74; I2 = 0%). Subgroup analyses showed comparable risks for gastrointestinal discomfort (RR = 1.04, 95% CI: 0.53–2.05; p = 0.90), fatigue (RR = 1.21, 95% CI: 0.43–3.37; p = 0.72), and allergic reactions (RR = 1.20, 95% CI: 0.53–2.70; p = 0.67). A non-significant trend toward reduced hormonal imbalances with Shoutai Pills (RR = 0.60, 95% CI: 0.33–1.09; p = 0.10). Significantly higher live birth rates (RR = 1.88, 95% CI: 1.50–2.35; p < 0.00001) and pregnancy retention rates (RR = 0.41, 95% CI: 0.33–0.51; p < 0.00001). Clinically meaningful reductions in TCM syndrome scores (MD = −2.35, 95% CI: −3.32 to −1.39; p < 0.00001) and serum D-dimer levels (MD = −0.25, 95% CI: −0.32 to −0.19; p < 0.00001).ConclusionShoutai Pills show promise as a safe and effective complementary therapy for recurrent miscarriage, significantly improving pregnancy outcomes and symptom relief.